Pseudocapacitive Lithium Storage in Three‐Dimensional Cobalt‐Doped MnO/Nitrogen‐Doped Reduced Graphene Oxide Aerogels as High‐Rate Anode Material. Issue 22 (8th October 2018) - Yao, Wei; Qiu, Weijie; Xie, Yu; Xu, Zixuan; Xu, Jianguang; Zhang, Dewei; Wen, Yongchun
Abstract: Structural design and modification are effective measures to improve the lithium storage performance of electrode materials. Herein, three‐dimensional (3D) porous Co‐doped MnO/nitrogen‐doped reduced graphene oxide aerogels (Co−MnO/NG‐G) have been prepared by successive self‐assembly processes, including the self‐assembly nucleation of Co−MnO on GO in H2 O/N, N‐Dimethylformamide (DMF) mixed solvent, and the 3D reduction‐assembly of hydrogels accompanied with nucleation‐inducing growth of Co−MnO nanocrystals. Due to high‐efficient electron/ion transport channels dating from the novel 3D porous microstructure and improved electron/ion conductivity deriving from doping MnO with Co, the 3D Co−MnO/NG‐G electrode demonstrates high pseudocapacitive lithium storage behavior with 88.3 % at 2 mV s −1 . As an anode in lithium‐ion battery, the 3D Co−MnO/NG‐G shows a high capacity of 982.8 mAh g −1 at 0.5 A g −1 after 100 cycles, outstanding rate capability with 424.0 mAh g −1 at 8 A g −1, as well as superior cycle stability with 508.9 mAh g −1 after 800 cycles at 4 A g −1 . This work demonstrates that the synergistic strategy between cation doping and 3D porous channels for electron/ion transport is an effective way to design high‐rate anode materials. Abstract : Three‐dimensional porous Co‐doped MnO/nitrogen‐doped reduced graphene oxide aerogels are prepared. The material exhibits shows pseudocapacitive lithium storage behavior and is thus a promising candidate to be used as high‐rate anode material in lithium‐ion batteries.